The Intervening Role of Village Financial Management on the Effect of Human Resources Competence and Village Government SOTK on the Success Level of Community Development and Empowerment Programs - Saiful Bahri; Nursaid Nursaid; Diyah Probowulan; Riyanto Setiawan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The purpose of this study is to determine the role of village financial management interventions on the influence of HR competencies and SOTK Pemdes on the success level of development programs and community empowerment throughout Asembagus District, Situbondo (East Java). This study applies a quantitative descriptive approach with a population of villages in Asembagus District. The sample was determined by purposive sampling technique. Data collection uses primary data from questionnaire data collection with village officials as respondents. Data analyzed used SEM-PLS with SmartPLS software. The results shown that HR competencies affects the success level of development programs, but does not affect the success level of community empowerment programs. The role of SOTK Pemdes affects the success level of development programs and the success level of community empowerment programs. The role of HR competencies and SOTK Pemdes affects village financial management. Village financial management affects the success level of development programs and community empowerment programs.